Comparative Study of Standard Four-Port, Three Port and Single Incision Laparoscopic Cholecystectomy Performed by a Single Surgeon in Nobel Medical College Teaching Hospital, Nepal - Sulaimankulov, Ruslan; Jolochieva, Gulmira (Birat Journal of Health Sciences, 2021)
Introduction: Laparoscopic Cholecystectomy is a standard operative procedure for patients with gallbladder diseases and is the most common laparoscopic procedure performed worldwide. The aim of this study is to analyze the different methods of laparoscopic cholecystectomies done by a single surgeon at Nobel Medical College Teaching Hospital. Objectives: The objective and aim of this study are comparing 4 port classic Laparoscopic Cholecystectomy (4PLC), 3 port (3PLC) and Laparo-Endoscopic Single-Site Cholecystectomy (LESC) performed by a single surgeon and correlate worldwide experience with outcomes in our institution. Methodology: The study includes retrospective analysis of 8192 patients who underwent elective laparoscopic Cholecystectomy (LC) from October 2010 to July 2020 performed by the single surgeon. All cases divided into 3 groups depending on the type of LC (4PLC, 3PLC, LESC). The data included the type of the surgery, gender, age, operative time, conversion and complication rate and duration of hospital stay. Results: The hospital stays, operation time and conversion rate decreased from group I to group III. Female patients out numbered the male ones (M:F=1:4). The hospital stays (3.4 days), operation time (35 min), conversion (0.4%) and complications (0.7%) rate decreased from Group of 4PLC to Group of LESC (1.5 days, 13 min, 0.1% conversion, 0.4% complication respectively) which is true for almost all other similar studies. Conclusion: The advantages of LESC include a better cosmetic effect and reduced chance of infections. It has been postulated to be superior in scarless surgery with added benefits of lower pain level and reduced need for analgesics, shorter hospital stays, quicker return to work and lower financial expenses.